Yahoo Web Search

  1. Given: q( r ) = r ^3+7r^2-24r+6 To find maximum/minimum, take the derivative: q'( r ) = 3r^2 + 14r - 24 Find the roots: 0 = 3r^2 + 14r - 24 r = (-14 +/- sqrt(14^2 - 4*3*(-24))) / (2*3) r = (-14 +/- sqrt(196 + 288)) / 6 r = (-14...

    1 Answers · Science & Mathematics · 15/07/2008

  2. A = 2pi r ^2 + 2pi( r )(h) First, move the A to the right hand side. That means one side will be zero. 2pi r ^2 + 2pi( r )(h) - A = 0 This is in the form of a quadratic, as...

    2 Answers · Science & Mathematics · 20/08/2008

  3. ∫9re^( r /4) If we make the substitution u = e^( r /4), we get du = 4e^( r /4), or du/4 = e^( r /4), which we can write as: 9/4...u(ln(u) - 1) Replacing the u's with e^ r /4: e^( r /4) * (ln(e^( r /4)) - 1), which is...

    1 Answers · Science & Mathematics · 13/03/2011

  4. R =A + C^2 R -A= C^2 + or - sqrt( R -A) =C C=sqrt( R -A) or C=-sqrt( R -A)

    2 Answers · Science & Mathematics · 30/08/2007

  5. r ' = dr/d∂ = ∂ sqrt(cos∂) - (2∂ sin∂) / 2sqrt(cos∂) = = (2∂ cos∂ - 2∂ sin...

    3 Answers · Science & Mathematics · 13/10/2008

  6. (7 r + 10)/ r ( r + 1)( r + 2) = A/ r + B/( r + 1) + C/( r + 2) A( r + 1...( r + 1) = 7r + 10 r = 0 --> 2A = 10 --> A = 5 r = -1 --> -B = 3 --> B = -3 r = -2 --> 2C = -4...

    1 Answers · Science & Mathematics · 03/01/2013

  7. r ^2 - 5r - 6r + 30 = 0 r ( r - 5) - 6( r - 5) = 0 ( r - 6)( r - 5) = 0 r - 6 = 0 or r - 5 = 0 r = 6 or r = 5

    3 Answers · Science & Mathematics · 06/02/2011

  8. ( r ^(2)-36)/(( r +6)^(2)) The binomial can be factored using the difference...difference of squares formula is a^(2)-b^(2)=(a-b)(a+b). (( r -6)( r +6))/(( r +6)^(2)) Reduce the expression by canceling out...

    5 Answers · Science & Mathematics · 06/03/2010

  9. Assume that R has a divisor of 0, say a different than 0, thus there exists c in R ...contradiction. If aba = a, then abab = ab thus abab -ab = 0, thus a( bab - b)=0, as R has no divisors of 0 we have that bab = b. Take any a...

    3 Answers · Science & Mathematics · 11/05/2012

  10. R (x) = -2x³ - 7x + 14 R (11) = -2(11)³ - 7(11) + 14 R (11) = -2(1331) - 77 + 14 R (11) = -2662 - 77 + 14 R (11) = -2725

    3 Answers · Science & Mathematics · 03/07/2008

  1. Try asking your question on Yahoo Answers